Auditoría financiera de control contable y financiero en la cooperativa de ahorro y crédito sierra centro Ltda., cantón la Maná, período 2012. Quevedo - Quevedo Ortega, María Aracely (2015)
The Financial Audit constitutes a tool of help for the administration of the entity and third persons been interested in the economic evolution, to determine whether the statements of financial position reasonably reflect the results of operations and compliance with the economic and financial provisions. The principal aim of this investigation is, to effect a financial audit of countable and financial control in the Cooperativa de Ahorro y Crédito Sierra Centro Ltda., Canton La Maná, period 2012, to check the reasonable of the information formed of the Financial statements, in order to issue a report that contains conclusions and recommendations tending to reach in the solution of opposing failings. For the development of the investigation methods were in use as inductively, deductively and descriptively because they are indispensable to execute the investigation. The Financial Audit was practiced on the basis of International Financial Reporting Standards (IFRS ) , in which errors were found in the balances of the following accounts: "Cash, Bank Accounts Receivable, loss exercise, management and collections, other operating revenues and various services," the balance shown on these accounts is different, real, hence in measuring risks the following results were obtained: high confidence level of 90 %, therefore a risk level found under 10%; inherent risk 25 %; 10 % control risk and detection risk is 10 %; giving as resulting 0.25% Risk Audit